Chromium Poisoning of LaMnO3‐Based Cathode within Generalized Approach1. Issue 4 (18th February 2013) - Yokokawa, H.; Horita, T.; Yamaji, K.; Kishimoto, H.; Yamamoto, T.; Yoshikawa, M.; Mugikura, Y.; Tomida, K.
Abstract Recent progress of the NEDO project on durability/reliability of SOFC stacks is reported with an emphasis on the achievement of Mitsubishi Heavy Industries' segment‐in‐series cells in which the lanthanum manganite cathode has been improved. Durability tests were made by CRIEPI on their cells with/without doped ceria interlayer to check plausible effects of microstructure change and of chromium poisoning. Improved cells exhibit essentially no degradation for 10, 000 h and also strong tolerance against the Cr contamination from stainless steel tubes. These features are discussed within the generalized degradation model developed inside the NEDO project. In particular, the extremely small overpotential can be considered to be effective in lowering the Cr poisoning by reducing the driving forces for the electrochemical Cr deposition at active sites. Insertion of doped ceria is also useful in preventing the Cr deposition or enhancing the volatilization of deposited Cr with cathodically emitted water vapors from ceria. Thermodynamic considerations reveal that the initial composition of LSM cathode is important to determine the microstructure change due to the chromium dissolution into the B‐sites in the perovskite lattice. Discussions are made on a role of doped ceria to prevent deterioration of Mn‐dissolved electrolyte by lowering the Mn dissolution into YSZ.